Purification and characterization of anti-phytopathogenic fungi angucyclinone from soil-derived Streptomyces cellulosae - Xu, Xindong; Zhao, Yang; Bao, Kang; Miao, Cuiping; Zhao, Lixing; Chen, Youwei; Wu, Shaohua; Li, Yiqing (Folia microbiologica, 2022)
Actinomycete strain YIM PH20352, isolated from the rhizosphere soil sample of Panax notoginseng collected in WenShang, Yunnan Province, China, exhibited antifungal activity against some phytopathogenic fungi. The structures of bioactive molecules, isolated from the ethyl acetate extract of the fermentation broth of the strain, were identified as rabelomycin (1) and dehydrorabelomycin (2) based on extensive spectroscopic analyses. Compound 1 exhibited antifungal activity against four tested root-rot pathogens of the Panax notoginseng including Plectosphaerella cucumerina, Alternaria panax, Fusarium oxysporum, and Fusarium solani with the MIC values at 32, 64, 128, and 128 μg/mL, respectively. Compound 2 exhibited antifungal activity against F. oxysporum, P. cucumerina, F. solani, and A. panax with the MIC values at 64, 64, 128, and 128 μg/mL, respectively. Based on the phylogenetic analyses, the closest phylogenetic relative of strain YIM PH20352 is Streptomyces cellulosae NBRC 13027 T (AB184265) (99.88%), so strain YIM PH20352 was identified as Streptomyces cellulosae. To the best of our knowledge, this is the first report of rabelomycin and rabelomycin-type antibiotics from Streptomyces cellulosae and their antifungal activity against root-rot pathogens of the Panax notoginseng.
Keywords: anthrachinony; Antifungal Agents; nemoci rostlin; Anthraquinones; Streptomyces cellulosae; houby; China; Isolation; Rabelomycin; Phylogeny; Fungi; Streptomyces; Plant Diseases; Čína; Panax notoginseng; Soil; půda; fylogeneze; antifungální látky; Dehydrorabelomycin